Pengaruh Kebijakan Deviden terhadap Volatilitas Harga Saham - Daffa Putra Alvaro; Nabila Amaro Laila Rosyda (ManBiz: Journal of Management and Business, 2024)
This study aims to examine the effect of dividend policy on stock price volatility. Dividend policy is measured through the proxies of dividend payout ratio, dividend yield and dividend per share. This research also adds control variables in the form of profit volatility and company growth. Stock price volatility was measured using Baskin's Model (1989). The sample used in this study is 49 financial sector companies listed on the Indonesia Stock Exchange from 2014-2019 and have met the qualifications of the research criteria. Determination of the sample is determined by purposive sampling method which produces 294 annual report data of companies engaged in the financial sector. This study uses panel data regression. This study was conducted with the aim of examining the effect of dividend policy variables with the proxies of dividend payout ratio, dividend yield and dividend per share on stock price volatility. This research resulted in dividend payout ratio, dividend per share and dividend yield significant negative effect on stock price volatility.